Leadership in recreation and leisure services - Goins, Terilyn J.; Cuthbertson, Brent 1961-; O'Connell, Timothy S. 1968- (Human Kinetics, 2015)
Leadership in Recreation and Leisure Services presents cutting-edge guidance and helps students apply their newfound knowledge as they prepare to enter the rapidly changing leisure services field. This text presents fresh insights on leadership from the most prominent voices in the field today. The contributors present a comprehensive look at modern leadership, identify the challenges future leaders will face, and reveal how future leaders can best prepare to meet those challenges. Leadership in Recreation and Leisure Services provides: a detailed look at the collaborative approach to leadership in leisure services that represents a new direction in the field; insight into classical leadership as well as innovative and modern leadership theory and best practices; and an understanding of the roles and functions students will fulfill as they enter the profession. The material, designed for undergraduate recreation and leisure services leadership courses, is presented in three parts. Part I explores personal leadership issues, including communication skills, negotiation strategies, and leadership styles. Part II delves into professional leadership, examining topics such as group dynamics, supervision practices, and team leadership. Part III explores organizational leadership, including internal and external leadership and professional development. The authors present new theories of leadership from research in the field of recreation and leisure. Several learning aids--including chapter-opening scenarios, key terms, glossary, references, and chapter-ending questions for reflection and discussion--appear throughout the text. In addition, each chapter features a Leisure Leaders sidebar that profiles a leader in the field who addresses preparation for the job, a peek at day-to-day work, and advice for aspiring leaders. And a Best Practices sidebar showcases an organization whose innovative leadership has led to positive organizational outcomes. Leadership in Recreation and Leisure Services helps students understand the range of leadership skills they need to develop for successful careers.